Functional and Clinical Characterization of Tumor-Infiltrating T Cell Subpopulations in Hepatocellular Carcinoma - Li, Jianguo; Zhou, Jin; Kai, Shuangshuang; Wang, Can; Wang, Daijun; Jiang, Jiying (Frontiers in Genetics, 2020)
Tumor-infiltrating T-lymphocytes are defined as T-lymphocytes that infiltrated into the tumor tissues, however, its composition, clinical significance, and underlying mechanism in hepatocellular carcinoma (HCC) and adjacent non-tumor tissues are still not completely understood. Herein, we collected marker genes of T cell subpopulations from previous study and estimated their relative infiltrating levels in HCC and adjacent non-tumor tissues. Specifically, the infiltrating levels of all the T cells were significantly reduced in HCC as compared with non-tumor tissues. Unsupervised clustering of the HCC samples by the T cell infiltrating levels revealed that the HCC samples could be clearly classified into two groups. The driver genes including PTK2B, ATM, PIK3C2B and KIT, and several CNAs were observed to be associated with reduced T cell infiltrating levels. Particularly, deletion of TP53 was more frequently occurred in low T cell infiltration HCC samples, and resulted in its downregulation and cell cycle progression, indicating that cell cycle progression was closely associated with reduced T cell infiltration. In contrast, for the samples with high infiltration T cells, its immune evasion might be regulated by the immune checkpoint regulators such as PD-1/PD-L1, and CTLA4. Moreover, Olaparib, one of PARP inhibitors, and immune checkpoint inhibitors might be therapeutic candidates for the samples from the two T cell infiltrating clusters. Clinically, the tumor-infiltrating levels of cytotoxic CD4 cell, Mucosal associated invariant T (MAIT) cell, and exhausted CD8+ T cell might be used as predictors for vascular invasion, recurrence and overall survival. Collectively, we systematically evaluated the clinical significance and potential molecular mechanism of tumor-infiltrating T cell subpopulations in hepatocellular carcinoma, which might broaden our insights into the immunological features of HCC and provide potential immunotherapeutic targets.